2003
DOI: 10.1242/jeb.00053
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of voltage-sensitive K+ and Ca2+ currents in neurons of the honeybee olfactory pathway

Abstract: The formation of olfactory memory is a multistage process that involves different areas of the insect brain. Olfactory conditioning of the proboscis extension reflex of the honeybee has proved to be a very powerful system for studying learningrelated neural mechanisms, enabling major neural elements of the olfactory and reward pathways in the honeybee brain to be identified (Erber et al., 1980;Hammer, 1993;Mauelshagen, 1993;Grünewald, 1999b;Hammer and Menzel, 1998) (for reviews, see Hammer, 1997;Menzel, 1999Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 77 publications
7
36
1
Order By: Relevance
“…In particular, they indicate that coincident EPSPs can summate supralinearly, favoring coincidence detection. Many of these observed subthreshold nonlinearities are likely attributable to the active conductances observed in KCs in culture (Schafer et al, 1994;Grunewald, 2003). These nonlinearities can amplify coincident EPSPs (as in the case of spikelets).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, they indicate that coincident EPSPs can summate supralinearly, favoring coincidence detection. Many of these observed subthreshold nonlinearities are likely attributable to the active conductances observed in KCs in culture (Schafer et al, 1994;Grunewald, 2003). These nonlinearities can amplify coincident EPSPs (as in the case of spikelets).…”
Section: Discussionmentioning
confidence: 99%
“…KCs and lateral horn interneurons (LHIs) (Perez-Orive et al, 2002) were modeled as a single compartment with channels governed by Hodgkin-Huxley kinetics as follows: (Sloper and Powell, 1979), and a transient (A-type) K ϩ current, I K,A (Grunewald, 2003); fast Na ϩ , I Na , and delayed rectified K ϩ , I K , currents were included to account for spike generation (Traub, 1982). Current kinetics were adjusted to 23°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that more and more α subunits as well as β subunit of VGPCs have been found in rat trigeminal ganglion (TG) (Gutman et al, 2005;Rasband and Trimmer, 2006). VGPCs show significant diversity in their biophysical and pharmacologic properties and there are at least two types of VGPC currents in sensory neurons: slow-inactivating potassium current (I K ), displaying slow or sometimes incomplete inactivation and fast-inactivating potassium current (I A ) exhibiting fast inactivation kinetics (Catacuzzeno et al, 2003;Gold et al, 1996;Grunewald, 2003;Stewart et al, 2003). VGPCs participate in the action potential (AP) and determine the excitability of cells by regulating the resting membrane potential, the threshold of AP and the frequency of AP firings (Rasband and Trimmer, 2006;Yost, 1999).…”
mentioning
confidence: 99%
“…Over the last ten years, honeybee nervous system electrical activity has been studied at the cellular and molecular level with electrophysiological techniques. A number of ionic currents have been characterized, mainly in neurons from two regions of the honeybee brain: mushroom bodies and antennal lobes (Goldberg et al, 1999;Grunewald, 2003;Kloppenburg et al, In the hive, a wide range of honeybees tasks such as cell cleaning, nursing, thermogenesis, flight, foraging and inter-individual communication (waggle dance, antennal contact and trophallaxy) depend on proper muscle activity. However, whereas extensive electrophysiological studies have been undertaken over the past ten years to characterize ionic currents underlying the physiological neuronal activity in honeybee, ionic currents underlying skeletal muscle fibre activity in this insect remain, so far, unexplored.…”
Section: Introductionmentioning
confidence: 99%